CONCEPT OF FOREIGN POLICY: A STUDY OF EFFECTING OR DETERMINING FACTORS - شمبش, د. علي (Dirasat in Economics and Business, 2022)
International politics consists of the sum of the foreign policies of different states. To be able to understand such Politics and / or policies one should examine the different and important, policy decisions. The foreign policy of any state is no longer considered to be exclusively a direct reaction to external stimuli or the result of changing conditions in world politics. It is rather a combination of the former and the internal circumstances of the state. As such, changes in a country's foreign policy may be, in part, a reflection of socio-economic development or the political-institutional changes in the country. Thus, it can be assumed that a combination of different factors make a state's foreign policy and, consequently a change of these factors may mean a change in the foreign policy behaviour of the state. The author of this_ article discusses four of ·these factors: geography, economy, public opinion, and the decision makers. The author does not intend this to be a case stud y, but, rather, attempts to clarify his arguments by giving axamples.